Tearing Apart the Land: Islam and Legitimacy in Southern Thailand, by Duncan McCargo. Singapore: NIAS/National University of Singapore Press, 2009, 235 pp. - Abu Talib Ahmad (Kajian Malaysia, 2013)
There is a considerable body of literature relating to the conflict in Southern Thailand (Pattani) contributed by Thais (both Malay Muslims and Thai Buddhists) and non-Thais including those from within the region and outside. These studies provide myriad interpretations on the violence waged by Malay Muslims against the Thai state in the south ranging from jihad to economic grievances and separatist aspirations. Tearing Apart the Land: Islam and Legitimacy in Southern Thailand provides new ground in the study of the conflict both in its central arguments and the sources consulted to offer a refreshing interpretation of this seemingly endless conflict which in the last nine years alone had claimed more than 3,000 lives. The book took a critical swipe at all concerned parties including former premier Thaksin Shinawatra (2001?2006) and the Thai security forces which it views as "core component of the problem." The book catalogues the damning repression and shortcomings of the Thai security forces in the way it handle the conflict with the militants who had invoked Islam as a rhetorical tool to galvanise support from various spectrum of Malay Muslims. These are contentious issues and open to debates. However the book provides fascinating reading for those interested in minority problems like those of Southern Thailand.